2007
DOI: 10.1140/epje/i2007-10235-y
|View full text |Cite
|
Sign up to set email alerts
|

Life and death of a fakir droplet: Impalement transitions on superhydrophobic surfaces

Abstract: We show that the equilibrium state of a water drop deposited on a superhydrophobic surface cannot be solely determined by its macroscopic contact angle but also depends on the drop size. Following the evolution of the interface of evaporating droplets, we demonstrate that the liquid can explore a succession of equilibrium conformations which are neither of the usual fakir nor Wenzel types. A comprehensive description of the transition between these wetting states is provided. To do so, we have taken advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
212
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(224 citation statements)
references
References 26 publications
9
212
3
Order By: Relevance
“…This was seen in simulations for drops of both cylindrical and spherical symmetry, and has recently been reported experimentally [19]. The depinning occurs to reduce the distortion of the interface from spherical.…”
supporting
confidence: 67%
“…This was seen in simulations for drops of both cylindrical and spherical symmetry, and has recently been reported experimentally [19]. The depinning occurs to reduce the distortion of the interface from spherical.…”
supporting
confidence: 67%
“…[16][17][18][19] Moulinet and Bartolo studied the droplet equilibrium state deposited on hydrophobic rough surfaces by using the real-time 3D imaging technique for different droplet sizes. 20) Erbil and Cansoy estimated the droplet penetration between the pillars by suggesting the modified Cassie-Baxter equation based on the geometry of square and cylindrical pillar patterns. 9) Although a number of studies have reported some important physics behind droplet wetting behavior on hydrophobic surfaces on the basis of experiments and modeling, clear understanding of transition wetting phenomena showing penetration of liquid between pillars is required for designing and controlling hydrophobic surfaces effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although wetting state has been extensively explored in previous reports, 13,14,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] the majority of these previous reports have focused on hydrophobic textured surfaces. Besides the wetting state was inferred from visible-wavelength images, making it difficult to identify the physical behavior at the vicinity of the micro-pillars on the test surfaces.…”
mentioning
confidence: 99%